Characterization of the basal inhibitor of class II transcription NC2 from Saccharomyces cerevisiae. - Goppelt, A (1996)
Human NC2 utilizes a unique mechanism of repression of transcription by associating with TBP and inhibition of preinitiation complex formation. Here we have cloned two genes from Saccharomyces cerevisiae and functionally characterized them as yeast NC2. We show that yeast NC2 binds to TBP as a heterodimer and represses RNA polymerase II transcription during assembly of the preinitiation complex. Yeast NC2 is highly homologous to its human counterpart within histone fold domains. C-Terminal regions previously discussed to be important for repression in man are in part not conserved. The human alpha but not the beta subunit efficiently heterodimerizes and represses transcription in combination with the corresponding yeast subunit. Yeast and human NC2 inhibit transcription in the presence of yeast and human TBP. However, repression is optimal within one species. The N-terminus of human TBP supports repression of transcription by human but not by yeast NC2.